Study of nonspecific binding of Escherichia. coli 0157:H7 on IgG immobolized on reduced graphene oxide electrodes with linear sweep voltammetry - Ahmed, Nasteho Ali
Microorganisms contamination of water is a major problem in the world. Escherichia coli is one of the significant waterborne pathogens which can cause severe health problems. The methods for detection and quantification of pathogens are time consuming, require advanced equipment and extensive procedure which is not applicable to be used in the field. Alternatively, electrochemical immunosensors for pathogen detection are used to overcome issue of specificity thanks to the antigen-antibody complex. However, antigen-antibody interaction suffers from nonspecific binding that can result in false signal response. To understand the effect of nonspecific binding, an electrochemical immunosensor was developed using immunoglobulin G (IgG) antibody not specific to E. coli O157:H7 and the nonspecific binding was analyzed via Linear Sweep Voltammetry (LSV). Screen-printed carbon electrodes (SPCEs) were modified with reduced graphene oxide (rGO/SPCE) for increased surface area for attachment of antibodies. Antibodies were immobilized by carbodiimide-assisted amidation reaction on rGO/SPCE (IgG/rGO/SPCE). Then, LSV was performed at different scan rates for different electrodes of SPCE, GO/SPCE, rGO/SPCE and IgG/rGO/SPCE. From the plot of the scan rate, effective surface area was calculated; rGO/SPCE was found to have the larger effective surface area of 68.5 mm2 in comparison to SPCE with surface area of 21.7 mm2. Additionally, LSV measurements were conducted for different E. coli concentrations where the electrodes with antibody (IgG/rGO/SPCE) were able to distinguish between the highest and lowest E. coli concentration (4 x 108 and 4 x 100 CFU ml-1) whereas electrode without IgG (rGO/SPCE) showed low distinction between highest and lowest E. coli concentration. Furthermore, FESEM images showed higher binding of cells to IgG/rGO/SPCE electrodes while rGO/SPCE electrodes show less attachment of E. coli. These results suggest that nonspecific binding of E. coli towards IgG can provide false signals in electrochemical measurements, and therefore it is necessary to provide appropriate strategies to avoid nonspecific binding that could lead to misinterpretation of measured signal. Future work will reduce nonspecific binding through modification of electrodes with specific antibody towards E. coli and using blocking agents such as bovine serum albumin (BSA).